Prevalence and associated risk factors of malaria among adults in East Shewa Zone of Oromia Regional State, Ethiopia: a cross-sectional study - Tadesse, Frew; Fogarty, Andrew W.; Deressa, Wakgari (BioMed Central, 2017)
BACKGROUND: Malaria is one of the most important causes of morbidity and mortality in sub-Saharan Africa. The disease is prevalent in over 75% of the country's area making it the leading public health problems in the country. Information on the prevalence of malaria and its associated factors is vital to focus and improve malaria interventions.